Dejados Atras: El Remanente: Al Borde del Armagedon - Book 10 - LaHaye, Tim F.; Jenkins, Jerry B. (Miami, Fl. : Editorial Unilit, 2002)
While a million people converge on the ancient city of Petra in preparation for the "Glorious Appearing," the Global Community begins to bomb the city, while believers elsewhere in the world face martyrdom at the hands of the Antichrist.
Keywords: Spanish language -- Reading materials